Bridging the chasm between theory and research/practice in Communication Science - Gertruida du Plooy (Communicare)
This article investigates the problems experienced by academics and higher education adult learners when required to conduct research in real-life situations, namely to find a logical link or bridge between theory and research methodology or practice. It is argued that a chasm is found to exist, due to factors such as alienation between theory and research/practice, the role of language, culture, and, the quest for objectivity. This is a reflective scrutiny addressing the utility criterion of theory- building, dialectical and relativist thinking, plus dispositions and skills that adult learners have to develop to promote creative and critical thinking. Thereafter, five generic dimensions of metatheoretical perspectives are offered as a possible means of bridging this chasm. The article concludes with specific recommendations, which future Communication curricula in higher education should address in order to facilitate bridging the divide between theory and research/practice.